Economic Viability of a 6.5kW Off-grid Solar PV with Various Sun-Tracking Systems in Northern Cyprus: A Case Study - Kassem, Youssef; Gokcekus, Huseyin; Hamad, Osama Abduljalil Mohammad; Fayid, Faed Mahmod Buojaylah (Engineering, Technology & Applied Science Research, 2023)
In this paper, an in-depth analysis of small-scale PV in Northern Cyprus is conducted for the first time at 37 locations in Northern Cyprus. No previous study has investigated the viability of off-grid PV systems with various sun-tracking systems in Northern Cyprus. In order to achieve this, NASA POWER data were used for the evaluation of the solar resource in the selected locations. The results showed that the selected locations are suitable for the installation of various scales of PV systems due to the high global horizontal solar radiation. The mathematical modeling method was utilized for the design and analysis of PV systems with various sun-tracking systems and for the assessment of their economic viability and feasibility. Energy production, capacity factor, payback period, and cost of energy production were calculated. The results indicate that the proposed systems are very promising for all the selected locations. The PV projects with a 2-axis sun-tracking system produce a large amount of energy and have a low electricity cost. It was found that the electrical energy cost of the developed systems was within the range of 0.4851-0.6641TL/kWh. The payback periods varied from 4.57 years to 8.49 years, depending on the type of solar PV panel and sun-tracking system. This study provides some useful recommendations for decision-makers regarding the development and deployment of PV energy technology in the country in order to achieve sustainable development goals.